WEBSIG UNTUK EFISIENSI INVENTARIS PENDAPATAN DAERAH SEKTOR PAJAK BUMI DAN BANGUNAN (STUDI KASUS DESA BENER, KECAMATAN SARADAN, KABUPATEN MADIUN) - Nugroho, Dimas Aprian; Handayani, Hepi Hapsari (Geoid, 2020)
Land and Building Tax (PBB) is one of the important local taxes for the region. PBB contribution to the amount of regional budget is quite high. Therefore, efficiency is needed in the management process. This needs to start from small publications such as the Village. By developing Geographic Information System (GIS) technology, of course it can be used to streamline the management of the PBB by using WebGIS technology. This study uses PBB data from the 2019 Bener Village Tax Assessment Book (DHKP) List, Maps of Madiun District from Office of National Land Agency (BPN), and Maps of Madiun District from the Bener Village Office. DHKP book data is processed into tables based on data on WebGIS. Land plot data in the field map is integrated into WebGIS spatial data. There are 1634 fields plots of land on WebGIS. From those 1634 fields, 1323 already have complete PBB information, 95 do not yet have NOP clarity, and 216 others have not been identified. The result show improvement of efficiency in the search for information on PBB object data. The object position data is obtained more easily, without using a large printed map which takes a lot of space. With this WebGIS, information on tourist attractions can be accessed anywhere and anytime through a computer or smartphone, as long as there is an internet connection so that it can facilitate the PBB management process.